Environmental variation predicts patterns of genomic variation in an African tropical forest frog - Miller, Courtney A.; Tasse Taboue, Geraud C.; Fokam, Eric B.; Morgan, Katy; Zhen, Ying; Harrigan, Ryan J.; Le Underwood, Vinh; Ruegg, Kristen; Clee, Paul R. Sesink; Ntie, Stephan; Mickala, Patrick; Mboumba, Jean Francois; et al. (Frontiers in Conservation Science, 2024)
Central African rainforests are predicted to be disproportionately affected by future climate change. How species will cope with these changes is unclear, but rapid environmental changes will likely impose strong selection pressures. Here we examined environmental drivers of genomic variation in the central African puddle frog (Phrynobatrachus auritus) to identify areas of elevated environmentally-associated turnover. We also compared current and future climate models to pinpoint areas of high genomic vulnerability where allele frequencies will have to shift the most in order to keep pace with future climate change. Neither physical landscape barriers nor the effects of past Pleistocene refugia influenced genomic differentiation.Alternatively, geographic distance and seasonal aspects of precipitation are the most important drivers of SNP allele frequency variation. Patterns of genomic differentiation coincided with key ecological gradients across the forest-savanna ecotone, montane areas, and a coastal to interior rainfall gradient. Areas of greatest vulnerability were found in the lower Sanaga basin, the southeastern region of Cameroon, and southwest Gabon. In contrast with past conservation efforts that have focused on hotspots of species richness or endemism, our findings highlight the importance of maintaining environmentally heterogeneous landscapes to preserve genomic variation and ongoing evolutionary processes in the face of climate change.